Generałowie polscy w obronie twierdzy Kars podczas wojny krymskiej - Chudzio, Hubert (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
In 1853, when a war – which is commonly referred to as Crimean War -between Russia and Turkey broke out, France and Great Britain took the Ottoman side. Taking advantage of the moment, the Poles counted on the regaining of their Independence. Numerous groups of Poles headed for Bosphorus to form legions and fight against Russia. Already at the beginning of the war, two Polish colonels, Feliks Breański and Ludwik Bystrzonowski, envoys of Hotel Lambert, made their way to Turkey. Recruited by the Ottoman Government, they received the ranks of Turkish generals and new names. The former took on the name of Szahin (Sokół – Hawk) Pasza, and the latter – Arsłan (Lew – Leo) Pasza. Bystrzonowoski was to form Christian formations of the so called Krakusi Kaukascy (Caucasian light cavalry). However, it was all to no avail. Both generals were sent to Anatolian army in Kars fortress in the north-eastern part of the region, near the Caucasus. There, together with English, French and Turkish commanders, they led the defence of the fortress and the manoeuvres in open field. Nevertheless, the headquarters were disrupted by continuous conflicts. The defeats against the Russian troops in the spring and summer of 1854, sparked further fierce conflicts among the competing foreign officers. The Polish generals were pointed at as culprits of the defeats, and – as a result – resigned and left Kars, and subsequently Turkey. The affairs in the Anatolian fortress were described by the press in London and Paris. The defence of Kars was by no means improved upon the resignation of Breański and Bystrzonowski from the fortress’ commandership and the Anatolian army continued to be poorly directed. Finally, on 28th of November 1855, the Russians seized Kars. Soon after, the fighting ceased and the conflict was to be resolved by the Conference of Paris in 1856.